Impact of prostate-specific antigen density in benign prostatic hyperplasia and prostate carcinoma. Preliminary results - (:unkn) unknown (Elsevier B.V., 1994)
In an attempt to enhance the success of prostate-specific antigen (PSA) in the diagnosis and staging of prostate carcinoma (PCa) the concept of PSA density (PSAD) has been introduced. Likewise a study to investigate the role of PSAD in 53 patients with PCa and 47 patients with benign prostatic hyperplasia (BPH) has been done. PSADs seemed to increase directly proportional to the grade in PCa and differed significantly between patient groups with BPH and localized + metastatic PCa, BPH and localized PCa, and localized PCa and metastatic PCa. Although 0.6 level for PSAD seemed to be a rational cut-off level in our study, this issue needs to be studied in multiple centers involving an increased number of patients for resolution.
Keywords: Benign prostatic hyperplasia; Prostate carcinoma; Prostate-specific antigen; Prostate-specific antigen density